2016
DOI: 10.1016/j.jnoncrysol.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of photosensitive AMTIR-1 chalcogenide thin layers deposited by electron beam deposition

Abstract: Amorphous Ge33As12Se55 films have been deposited by electron beam physical vapor deposition and their optical properties have been studied using reverse engineering on spectrophotometric measurements. Definition of the different optical constants were made by Tauc-Lorentz model allowing simultaneous characterization in high and low absorption area. Moreover an investigation of the layer's photosensitivity with an exposure wavelength at ~808 nm has been carried out and reveals a photo-bleaching effect generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A relative precision of the thickness better than 1 nm and an absolute precision within 2% was achieved using this technique. Finally, previous expertise [43] has shown that by adapting properly the deposition parameters, it is possible to keep a composition close to that of a raw material, securing that the properties of the initial material will be maintained. We fabricated two samples with two different GST thicknesses: the first (sample 1) with 53 nm and the second one (sample 2) with 58 nm.…”
Section: Discussionmentioning
confidence: 99%
“…A relative precision of the thickness better than 1 nm and an absolute precision within 2% was achieved using this technique. Finally, previous expertise [43] has shown that by adapting properly the deposition parameters, it is possible to keep a composition close to that of a raw material, securing that the properties of the initial material will be maintained. We fabricated two samples with two different GST thicknesses: the first (sample 1) with 53 nm and the second one (sample 2) with 58 nm.…”
Section: Discussionmentioning
confidence: 99%
“…A relative precision of the thickness better than 1 nm and an absolute precision within 2% was achieved using this technique. Finally, previous expertise [ 52 ] has shown that by properly adapting the deposition parameters, it is possible to keep a composition close to that of a raw material, securing that the properties of the initial material will be maintained. Thin‐films of ITO were deposited by magnetron sputtering in a partial Ar/O 2 atmosphere and the substrate was kept at 250 °C during deposition.…”
Section: Methodsmentioning
confidence: 99%
“…It is composed in molar percent with 33% of germanium, 12% of arsenic and 55% of selenium and was provided by Amorphous Material Company. AMTIR-1 was already deposited as thin films by pulsed laser deposition [7], thermal or e-beam evaporation, and showed excellent optical properties [8]. Layers from AMTIR-1 were shown to be excellent candidates for the production of various optical elements such as ring resonators [9]… We recently showed that these layers are also a good candidate for the production of a new kind of optical elements [10].…”
mentioning
confidence: 99%
“…The residual pressure inside the vacuum chamber was around ~10 -6 mbar and the deposition rate was 10 ± 1 A/s. In a previous works [8] using those parameters, we first demonstrated that AMTIR-1 materials provide broad transparency range above 850 nm, high refractive index (n = 2.74 @ 1 µm) and photosensitive properties such as photo-bleaching effect. This effect occurs into the AMTIR-1 layers when exposed to a light with a wavelength whose energy is below the bandgap.…”
mentioning
confidence: 99%